Seismic Vulnerability Assessment of the Cliff-Attached Buildings Equipped with Energy Dissipation Devices Under Obliquely Incident Seismic Waves - Zhuoxin Yang; Dewen Liu; Jiayu Zhou; Li Zhang; Wenyuan Liao (Buildings)
Cliff-attached structures are structures attached to slopes and connected tightly, which is particularly complex to analyze due to the foundations’ unequal grounding and the lateral stiffness’ irregularity. In rare earthquakes, seismic waves are usually obliquely incident on the foundation at a certain angle. Therefore, it is not appropriate to consider only seismic waves’ vertical incidence, and it is necessary to consider multi-angle oblique incidence. In this paper, based on the theory of viscous-spring artificial boundary and the principle of equivalent nodes at the interface of oblique incidence of ground shaking P-waves, and combined with the dynamic properties related to Buckling-Restrained Brace, the numerical models of slopes and two kinds of cliff-attached structures considering the slope amplification effect and soil-structure interaction are established. The dynamic response of the obliquely incident seismic waves under the action of the cliff-attached vibration reduction structure is studied in depth, and the additional effective damping ratios of the nonlinear energy-dissipated units based on the deformation energy are compared and analyzed. It is shown that under the four oblique incidence angles of incidence (compression waves in the vertical plane) studied in this paper, the seismic dynamic response and damage degree peaked at an angle of incidence of 60°, with a tendency to increase and then decrease with increasing angles of incidence. The ability of an energy-dissipating vibration reduction device to change structural vibration characteristics decreases with an increase in incidence angle. The difference between the total strain energy of the structure in the X-direction (Transverse slope direction) and Y-direction (Down-slope direction) and the total energy dissipation of the dissipative components is obvious, with the X-direction being about 10 times that of the Y-direction.